Employers’ perception on engineering, information and communication technology (ICT) students’ employability skills - Md Saad, Mohd Shamsuri; Robani, Anidah; Jano, Zanariah; Abdul Majid, Izaidin (World Institute for Engineering and Technology Education, 2013)
This article is based on the findings of a survey of employers having Universiti Teknikal Malaysia Melaka (UTeM) engineering and ICT students undergoing industrial training at their organisations. The study seeks to explore the employers’ perceptions of the employability skills that technical students need to possess, as well as assessing the employers’ level of satisfaction with the students’ employability skills. A 13-item scale of engineering employability skills adopted from the Engineering Accreditation Council (EAC) manual and the Future of Engineering Education Report 2007 were utilised as the main instrument to gauge the employers’ perception of UTeM’s students. The findings revealed that problem-solving, tool handling competency and presentation skills feature highly amongst the skills demanded of students by employers. The findings are useful for the University to understand how to equip its students and graduates according to the requirements of industry and to ensure they are highly employable after graduating from the University.